2013
DOI: 10.1186/1748-5908-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of the Influences on Patient Safety Behaviours Questionnaire

Abstract: BackgroundUnderstanding the factors that make it more or less likely that healthcare practitioners (HCPs) will perform certain patient safety behaviors is important in developing effective intervention strategies. A questionnaire to identify determinants of HCP patient safety behaviors does not currently exist. This study reports the development and initial validation of the Influences on Patient Safety Behaviors Questionnaire (IPSBQ) based on the Theoretical Domains Framework.MethodsTwo hundred and thirty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 32 publications
3
69
0
Order By: Relevance
“…These results correspond with Taylor et al [36,63] who found good discriminant validity of TDF domains in a questionnaire measuring influences on patient safety behaviors [36] and in the Determinants of Physical Activity Questionnaire [63]. While Taylor et al [36,63] used specific items ( i.e. , related to a specific application), our items are generic and allow for application within a range of different contexts in which implementation research takes place.…”
Section: Discussionsupporting
confidence: 93%
“…These results correspond with Taylor et al [36,63] who found good discriminant validity of TDF domains in a questionnaire measuring influences on patient safety behaviors [36] and in the Determinants of Physical Activity Questionnaire [63]. While Taylor et al [36,63] used specific items ( i.e. , related to a specific application), our items are generic and allow for application within a range of different contexts in which implementation research takes place.…”
Section: Discussionsupporting
confidence: 93%
“…At the time of writing the questionnaire, the TDF had only been applied in two quantitative studies [40,41] and demonstrated varying degrees of internal consistency in domains and either one [41] (propensity to act) or three [40] (capability, opportunity, motivation) factor explanatory models. Subsequent quantitative applications [22,52,53] have shown good discriminant validity, collated a wider array of domain items, and demonstrated levels of internal consistency similar to our findings.…”
Section: Study Strengthssupporting
confidence: 82%
“…The ‘nature of the behaviour’ domain was also excluded; Michie et al . explain that this domain is accorded to a different order as it describes the dependent variable, in this case, taking medicines as prescribed . It is therefore not treated as a domain of behaviour change, but its constructs such as habits were considered throughout the mapping task.…”
Section: Resultsmentioning
confidence: 99%